KNOWLEDGE, ATTITUDE AND PRACTICE TOWARDS COVID-19 FOR ETHNIC MINORITY PEOPLES IN COMMUNITY OF GIA LAI PROVINCE (Vietnam Journal of Community Medicine, 2022)
Objective: Coronavirus 2019 (COVID-19) is currently a global health threat and an international public health emergency. As of 21 December 2021, 97.8 million cases with more than five million deaths were recorded worldwide while in Vietnam more than 1,5 million confirmed cases and 28.616 deaths were reported. Hence, the aim of the present study was to determine the magnitude of knowledge, attitude, and practice toward COVID-19 for ethnic minority peoples in Gia Lai, Vietnam.Subjects and methods: A health institution-based cross-sectional study was conducted among the 309 study population in Community from September 1 to December 20, 2021. A structured questionnaire was used to obtain information related to sociodemographic characteristics, knowledge (twelve questions), attitude (three questions) and practice (three questions). Both bivariable and multivariable logistic regression analyses with a 95% confidence interval were used to identify factors associated with poor knowledge and practice.Results: Out of the total study participants 64.31% were madams, 95.2% of them were living in countryside areas. The magnitude of poor knowledge, poor attitude and poor practice was 21,2%; 27,4% and 35% respectively. Poor knowledge had statistically significant association with attitude and practice. Alarmingly high poor knowledge, negatively skewed attitude, and poor practice regarding the COVID-19 pandemic was indicated.Conclusion: Health education programs aimed at mobilizing and improving COVID-19-related knowledge, attitude, and practice are urgently needed, especially for those who are illiterate, having travel and contact history, or generally among underprivileged populations.
Keywords: COVID-19; Gia Lai; ethnic minority peoples; attitude; knowledge; practice; public health.